2020
DOI: 10.1111/risa.13491
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for Survival of Escherichia coli O157:H7 and Generic E. coli in Soil Amended with Untreated Animal Manure

Abstract: This study aimed at developing a predictive model that captures the influences of a variety of agricultural and environmental variables and is able to predict the concentrations of enteric bacteria in soil amended with untreated Biological Soil Amendments of Animal Origin (BSAAO) under dynamic conditions. We developed and validated a Random Forest model using data from a longitudinal field study conducted in mid-Atlantic United States investigating the survival of Escherichia coli O157:H7 and generic E. coli i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The presence of these microorganisms in vegetables could be due to contamination at the farm level and/or cross-contamination during handling, processing, and storage. At the farm level, the presence of these microorganisms is often associated with fecal contamination, use of untreated irrigation water, inadequate composting of manure, and poor human handling as well (Atidégla et al, 2016;Carstens et al, 2019;Pang et al, 2018Pang et al, , 2020. Note that their presence could also be influenced by environmental conditions, such as temperature, wind speed, and precipitation (Pang et al, 2018(Pang et al, , 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these microorganisms in vegetables could be due to contamination at the farm level and/or cross-contamination during handling, processing, and storage. At the farm level, the presence of these microorganisms is often associated with fecal contamination, use of untreated irrigation water, inadequate composting of manure, and poor human handling as well (Atidégla et al, 2016;Carstens et al, 2019;Pang et al, 2018Pang et al, , 2020. Note that their presence could also be influenced by environmental conditions, such as temperature, wind speed, and precipitation (Pang et al, 2018(Pang et al, , 2020.…”
Section: Resultsmentioning
confidence: 99%
“…At the farm level, the presence of these microorganisms is often associated with fecal contamination, use of untreated irrigation water, inadequate composting of manure, and poor human handling as well (Atidégla et al, 2016;Carstens et al, 2019;Pang et al, 2018Pang et al, , 2020. Note that their presence could also be influenced by environmental conditions, such as temperature, wind speed, and precipitation (Pang et al, 2018(Pang et al, , 2020. Thus, a proper application of good agriculture practices by farmers would prevent and reduce bacterial contamination of vegetables at preharvest production.…”
Section: Resultsmentioning
confidence: 99%
“…Third, soil moisture can also determine the ability of a pathogen to persist and survive in soil. For example, one study found that pathogenic E. coli populations often peak following rainfall events [65] and another reported that rainfall and soil moisture were key factors influencing pathogenic E. coli survival [66]. Conversely, microbial growth decreases when soil becomes drier, as dry soils can impede microbial mobility, limit nutrient availability and slow nutrient diffusion through membranes [46].…”
Section: (B) How Soils Regulate the Establishment And Suppression Of Human/animal Pathogensmentioning
confidence: 99%
“…Other workers analyzing the same large data set from Sharma et al (11) showed that soil moisture was highly predictive of E. coli levels as well. A number of factors related to rainfall were also relatively highly predictive of E. coli levels in soils containing BSAAO, including: number of days or rainfall since the previous day of analysis for E. coli levels (sampling day), average daily precipitation since the previous sampling day, average daily precipitation over the week prior to the sampling day, and days of rain over the week prior to the sampling day (25). Previous work has shown that moist soil supported the conversion of ammoniacal nitrogen (NH 3 -N) to NO 3 (26).…”
Section: Downloaded Frommentioning
confidence: 99%